Prevalence of Loss of Smell and/or Taste and other Otorhinolaryngology Symptoms in COVID-19 Patients - Shrestha, I.; Mishra, A.; Mishra, A.; Bista, M.; Acharya, J. (Kathmandu University Medical Journal, 2021)
Background Loss of smell and/or taste have been described in COVID-19 patients. Studies have not been conducted to evaluate the loss of smell and/or taste in the context of Nepal. Objective To investigate the prevalence of Ear, Nose and Throat related symptoms and assess smell and taste disorders in laboratory-confirmed SARS-CoV-2 patients. Method This prospective cross-sectional study evaluated patients from September 2020 to March 2021 with preceding COVID-19 diagnosis from a tertiary centre in Kathmandu. COVID-19 positive patients visiting out-patient department, quarantined or admitted were included. Patients were given questionnaire consisting of demographic data, history of smoking and evaluation of presenting symptoms. Loss of smell and taste were subjectively tested and followed up via telephone for ten weeks to evaluate for recovery time and degree of recovery. Result A total of 226 patients participated in the study, 18-92 years old (mean age, 36.77 ± 15.23 years; 53.5% males, 69% non-smokers). Majority of the patients had Myalgia (n = 128, 56.6%) as their presenting symptoms followed by fever (n = 122, 53.9%), loss of smell (n = 117, 51.7%), cough (n = 107, 47.34) and sore throat (n = 102, 45.1%). Loss of sense of smell and taste was reported in 51.8% and 42% respectively. The association between loss of sense of smell and taste was statistically significant (p < .001). All patients had some degree of recovery with 64.1% recovery of smell and 64.2% recovery of taste within 14 days of onset of symptoms. The mean recovery time for sense of smell and taste was 14.34 ± 9.82 days and 15.03 ± 10.06 days, respectively. Conclusion Olfactory and gustatory dysfunctions are cardinal features of COVID-19. They recover spontaneously along with other symptoms within few weeks. The absence of smell or taste in times of pandemic can be suggestive of potential COVID-19 infection and be used as a screening tool for early diagnosis and reduce transmission of the infection.